Adrenocortical Malignancy and Hypercortisolism Manifested as Uncontrolled Hypertension : A Case Report and Review of Literature - Hasan, Md Nazmul; Rahman, Md Atikur; Rahim, Md Abdur; Ahmed, Quazi Mamtaz Uddin; Islam, Md Syedul (University Heart Journal, 2018)
Adrenocortical carcinoma is one of the rare malignancies with worst prognosis. It presents with mass effects and less commonly with features of hormone excess (About 60% of all adrenocortical carcinoma’s). Hormonally active adrenocortical carcinomas most commonly secretecortisol while the co-secretion of multiple steroid hormones is rare.We report the case of a 47- year-old woman presenting with weakness of lower limbs, truncal obesity and growth of terminal hair on upper lip for one and half months. She was diagnosed Cushing Syndrome due to malignant adrenal tumour by abdominal CT scan and serum cortisol and ACTH. This case was inoperable and finally she received palliative chemotherapy.In cases of adrenocortical malignancy hormonal status should be investigated as the pattern of hormone secretion may be a clue to the malignancy of anadrenal lesion. In addition, more data are needed to clarify the clinical and prognostic significance ofthe combined production of all adrenocortical hormones affecting either the survival or the quality oflife of patients with adrenocortical malignancy. University Heart Journal Vol. 12, No. 2, July 2016; 95-97